2019
DOI: 10.1186/s40538-019-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi Beauveria bassiana Balsamo accelerates growth of common bean (Phaeseolus vulgaris L.)

Abstract: Background: Common bean (Phaseolus vulgaris L.) is a source of antioxidant-containing vegetable protein that is beneficial to human health. The intense cultivation of common bean may result in environmental degradation. Thus, environmentally friendly cultivation methods that use an endophyte to improve productivity are needed. An entomopathogenic fungus, Beauveria bassiana, can serve as an endophyte that stimulates the growth of Gossypium. Therefore, we isolated and identified B. bassiana and also examined its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…The root lengths varied significantly among treatments, and the shortest length was observed in plants exposed to the highest concentration of fungal treatment, which may suggest that fungus might have had a negative effect on root length. In a more recent study, B. bassiana inoculation had a positive influence on plant growth parameters including root length of common beans ( Phaeseolus vulgaris ) (Afandhi et al., 2019). Nevertheless, the colonization of plant tissues by fungal endophytes can be influenced by many factors, such as inoculation method, species and fungal strain (Muvea et al., 2014; Afandhi et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The root lengths varied significantly among treatments, and the shortest length was observed in plants exposed to the highest concentration of fungal treatment, which may suggest that fungus might have had a negative effect on root length. In a more recent study, B. bassiana inoculation had a positive influence on plant growth parameters including root length of common beans ( Phaeseolus vulgaris ) (Afandhi et al., 2019). Nevertheless, the colonization of plant tissues by fungal endophytes can be influenced by many factors, such as inoculation method, species and fungal strain (Muvea et al., 2014; Afandhi et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, B. bassiana inoculation had a positive influence on plant growth parameters including root length of common beans ( Phaeseolus vulgaris ) (Afandhi et al., 2019). Nevertheless, the colonization of plant tissues by fungal endophytes can be influenced by many factors, such as inoculation method, species and fungal strain (Muvea et al., 2014; Afandhi et al., 2019). Fungal endophytes might affect the nutrient cycle and uptake of nutrients from the soil by plants (Saikkonem et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…bassiana is suppressing the plant defense against aphids via defense pathway cross talk. Several studies have found that EEF benefit plant growth [39–44], and that EEF can translocate nitrogen to their plant host [45]. Specifically, endophytic B .…”
Section: Discussionmentioning
confidence: 99%
“…Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae) is a soil borne fungus that attacks an extensive host range of insects at all stages of development (Ownley et al, 2004). In addition to insecticidal activity, B. bassiana has been found to protect plants against certain plant pathogens (Ownley et al, 2004; as well as to function as a biofertilizer (Vega, 2018;Afandhi et al, 2019). Different isolates of B. bassiana have been reported as naturally occurring endophytes in a variety of plant species such as tomato, potato, maize, cotton, cucumber, melon, and rice (Vega, 2008;Brownbridge et al 2012;Vidal, Jaber, 2015).…”
Section: Introductionmentioning
confidence: 99%